Slavic Music or In Crudo Village Tradition? - Maria Małanicz-Przybylska (Muzikološki Zbornik)
This article analyzes the debate sparked by the soundtrack to the film The Peasants. It presents two opposing points of view: that of the In Crudo community, dedicated to reconstructing ‘authentic’ Polish village music, and that of enthusiasts of the world music scene, interested in the broader, intercultural, Slavic music idiom. Drawing on these perspectives, the author reflects on what traditional music is and who needs it in Poland today.